2000
DOI: 10.1111/j.1651-2227.2000.tb00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Escherichia coli infections: concerns regarding resistance to current therapy

Abstract: Ampicillin and gentamicin resistance is emerging in neonatal E. coli isolates from invasive infection. Current- empiric management of neonatal sepsis requires re-evaluation given changing antimicrobial susceptibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 5 publications
0
24
2
Order By: Relevance
“…However, differences in the percentages of Gram-resistant isolates from 3% [3] to 50% [5,24] among EONS strains and from 0% [19] to 16% [4] among LONS strains seem to be present among the different studies [3,5,17,24]. Quinolone resistance is frequently associated with extended-spectrum cephalosporin resistance in Enterobacteriaceae [25]; however, this association was not found in the present study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, differences in the percentages of Gram-resistant isolates from 3% [3] to 50% [5,24] among EONS strains and from 0% [19] to 16% [4] among LONS strains seem to be present among the different studies [3,5,17,24]. Quinolone resistance is frequently associated with extended-spectrum cephalosporin resistance in Enterobacteriaceae [25]; however, this association was not found in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…However, there are also several studies that have demonstrated that this relationship does not exist [20]. Friedman et al [5] postulated that the presence of prolonged rupture of the fetal membranes and an elevated maternal temperature during labor, which is suggestive of chorioamnionitis, are also perinatal variables associated with the emergence of resistant E. coli isolates. In addition, a lower gestational age and birth weight are neonatal variables associated with the appearance of these resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some concern arose from the concomitant emergence of neonatal infections with ampicillin-resistant Escherichia coli [12]. This adverse effect of any widespread antibiotic therapy was dreaded from the outset of the prophylaxis policies [1,2] and has indeed been observed by several authors in the past decade [13][14][15][16][17][18][19]. Awareness of all changes in local bacterial epidemiology is of uppermost importance to any neonatal care center in order to adapt the presumptive antibiotic therapy used in the case of suspected neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, there has been an increase in resistance of Escherichia coli to gentamicin and tobramycin. 6,7 In 2011, our institution-specific susceptibilities to gentamicin and tobramycin were 90% and 91%, respectively. Because of decreased susceptibility rates with gentamicin and tobramycin, prescribers have opted to change the aminoglycoside of choice for neonatal sepsis to amikacin, with an E coli 99% susceptibility rate in our NICU.…”
Section: Introductionmentioning
confidence: 99%